Automatically Analyzing Large Texts in a GIS Environment: The Registrar General's Reports and Cholera in the 19th Century. Issue 2 (14th November 2014) - Murrieta‐Flores, Patricia; Baron, Alistair; Gregory, Ian; Hardie, Andrew; Rayson, Paul
Abstract The aim of this article is to present new research showcasing how Geographic Information Systems in combination with Natural Language Processing and Corpus Linguistics methods can offer innovative venues of research to analyze large textual collections in the Humanities, particularly in historical research. Using as examples parts of the collection of the Registrar General's Reports that contain more than 200, 000 pages of descriptions, census data and vital statistics for the UK, we introduce newly developed automated textual tools and well known spatial analyses used in combination to investigate a case study of the references made to cholera and other diseases in these historical sources, and their relationship to place‐names during Victorian times. The integration of such techniques has allowed us to explore, in an automatic way, this historical source containing millions of words, to examine the geographies depicted in it, and to identify textual and geographic patterns in the corpus.